Peramalan Produksi Ikan Laut di Kabupaten Pesisir Selatan Menggunakan Metode Pemulusan Eksponensial Tripel Tipe Brown - Rimpi Oktaria; Dewi Murni; Helma Helma (UNIVERSITAS NEGERI PADANG, 2019)
Abstract – Indonesia is a maritime country that has a lot of potential wealth of the sea, one of them is fish production. In West Sumatra, Pesisir Selatan is one of the Region that have a lot of fish production. It is beneficial for the local government to increase the GDP. Therefore, Pesisir Selatan marine fish production for the next few years needs to be foreseen for the government to make planning and appropriate action so the local revenue and foreign exchange could be improved. The purpose of this research was to obtain a forecasting model and predict fish production of Pesisir Selatan in 2015 until 2019. The forecasting method used is triple exponential smoothing method of Brown type. Based on the research results, it is estimated the Pesisir Selatan fish production for 2015 to 2019 has increased.Keywords – Fish Production, Forecasting, Tripel Exponential Smoothing, Brown Type